Still enigmatic: Plasmodium oocysts 125 years after their discovery - Hentzschel, Franziska; Frischknecht, Friedrich (Trends in parasitology, 2022)
One hundred and twenty five years ago, in August 1897, Ronald Ross discovered forms of the malaria parasite in the gut of two mosquitoes. Shortly afterwards, Giovanni Battista Grassi established how the transmissive forms of the parasite, sporozoites, develop in these Plasmodium oocysts. Today, we still understand surprisingly little about the molecular processes governing oocyst biology.
Gesehen am 17.10.2022